Quantitative evaluation of fibrosis in idiopathic orbital inflammatory pseudotumor by IVIM-DWI - Pu, Jian; Xu, Xing; Wang, Peng; Su, Wei; Shao, Juwei; Yang, Yinhua; Li, Mingqin; Li, Jianbo (Frontiers in Ophthalmology, 2025)
ObjectiveTo quantitatively evaluate the degree of fibrosis in Idiopathic Orbital Inflammatory Pseudotumor (IOIP) using Intravoxel Incoherent Motion Diffusion-Weighted Imaging (IVIM-DWI).MethodsTwenty eight patients (32 eyes) with idiopathic orbital inflammatory pseudotumor were pathologically diagnosed in the Affiliated Hospital of Yunnan University from August 2019 to August 2024. Routine orbital MRI plain scan and ivim-dwi scan were completed before surgery, and the true diffusion coefficient (d), pseudo diffusion coefficient (d*) and perfusion fraction (f) were obtained. According to the proportion of chronic inflammatory cells and fibrous tissue components in postoperative histopathological sections, it was defined that fibrous cells accounted for less than 10% of the total number of cells as negative (–), and > 10% as positive (+), of which 10%%25% were +, 25%%50% were + +, 50%%75% were + + +, and > 75% were + + +. Taking the proportion of fibrocytes in histopathological sections as the standard of fibrosis degree, the correlation between ivim-dwi parameters and the proportion of fibrocytes in pathological sections was analyzed. Data were analyzed by SPSS 19.0 statistical software package, and P < 0.05 was considered statistically significant.ResultsAmong 28 cases (32 eyes) with idiopathic orbital inflammatory pseudotumor, there was no statistical difference between gender, age and the degree of IOIP fibrosis (P > 0.05). There was a statistically significant difference between the proportion of IOIP fiber composition and the D value and F value in IVIM-DWI parameters (P < 0.05), and the sensitivity of F value was higher than D value in the comparison of the two parameters combined with ROC curve analysis; There was no statistical difference between the D * value and the degree of fibrosis (P > 0.05).ConclusionThe D value and F value of IVIM-DWI showed a correlation with the proportion of IOIP fiber components, and the sensitivity of F value was higher than D value. Ivim-dwi examination parameters can be used as quantitative and objective indicators to evaluate the degree of fibrosis of lesions before IOIP.